Activization of Students Learning and Cognitive Activity - E. Gazizov, Svetlana; R. Gazizov, Evgeny; G. Kiseleva, Nataliya; N. Zinnatullina, Alsu (International Journal of Psychosocial Rehabilitation, 2024)
Activation of students’ learning and cognitive activity remains the key problem in the educational process. The learning and cognitive activity of students involves the development of self-dependence and creative activity in the process of learning. The activity of students means the consciousness of execution of educational tasks, the systematic character of training, the desire to increase the level of knowledge, etc.